Assessment of therapeutic and antimocrobial effects of local plants on bacterial diseases in red hybrid tilapia (Oreochromis sp.) - Manaf, Sharifah Raina (2016)
Currently, aquaculture is regarded as one of the potential strategic industries for Malaysia. The percentage on its production increases year by year. The growth are obvious due to obstacle in continuous dependent on finite stocks of protein source from wild-caught fish which is shown to be over-exploited or near to be depletion. One of main problem in aquaculture is outbreaks of infectious diseases which has incurred big losses to the industry. Herbal medicine has been used in most part of the world as an alternative medicine for human being and domestic animals. The plant compounds have been shown to be beneficial and rich in a wide variety of phytonutrients, and thus used as chemotherapeutics and feed additives. Hence, the general objectives of this study were to determine the effect of herbal supplementation on the growth performance, disease resistant, disease treatment in Red hybrid tilapia (Oreochromis sp.). Six extracts of Vitex trifolia, Aloe vera, Strobilanthes crispus, Clinacanthus nutans, Pereskia grandifolia and Peperomia pellucida were determined for phytochemical properties and their antibacterial activities against common freshwater pathogens i.e. Streptococcus agalactiae, Aeromonas hydrophila and Enterobacter cloacae. Qualitatively screening of phytochemical properties in herbs were determined for flavonoids, tannins, saponin, alkaloids steroid and glycoside. The results showed presence of flavonoid in all plant extracts. For the antimicrobial activity, the aqueous and methanolic extracts were tested by using disk diffusion method. Antimicrobial assay of methanolic extracts (25 to 100 mg/mL) showed effectiveness against the pathogenic bacteria. Comparatively, all aqueous extracts did not show any antimicrobial activity. Moderate antibacterial activity was shown by the methanolic extracts of V. trifolia, A. vera and S. crispus while weak antimicrobial activity was shown by C. nutans, P. grandifolia and P. pellucida. From the antimicrobial result, three potential plant extracts namely V. trifolia (VTE), S. crispus (SCE) and A. vera (AVE) were test for toxicity and feeding experiment. The cytotoxicity test using Artemia salina (45.9 - 66.7 μg/mL) and BF-2 fish cell line (85.0 - 120.50 μg/mL). The median lethal dose (LD50) value in Oreochromis sp. injected intraperitoneal were equivalent to 2.67 X 107 CFU/mL (S. agalactiae), 3.10 X 106 CFU/mL (E. cloacae) and 3.75 X 105 CFU/mL (A. hydrophila). Oreochromis sp. were fed with diet supplemented with VTE, SCE and AVE at 2g/kg, 5g/kg, 7g/kg and 9g/kg for 45 days, followed by challenged with 0.1 ml of 107 CFU/ml S. agalactiae. The results showed Oreochromis sp. supplemented with VTE-7 was the best growth promoter among treatments. It showed 57.3% in body weight gain with 100% survivability. For haematological the value of Hb after challenged with S. agalactiae showed significant different (P<0.05) compared to control except in SCE-2 and SCE-7. While, in WBC value showed significant different (P<0.05) except in AVE-5 and AVE-7. In MCV value showed significant different except in SCE-5, AVE-9 and in MCHC value showed significant except in VTE-2 and SCE-5. In biochemical parameters of blood, there was significant different in ALT value observed in fish fed with VTE-2, VTE-5, VTE- 7, SCE-2, SCE-5, SCE-7, AVE-5 and AVE-7 compared to control (infected). In AST value showed significant different (P<0.05) in VTE-5, VTE-7, SCE-9, AVE- 2 and AVE-7 compared to control (infected). Fish fed with SCE-5 was the best for the disease resistant showed the highest level of WBC value indicated increase immune responses and the ability of the fish to fight S. agalactiae. In histology examination of different selected herbal extracts showed mild degeneration in liver and kidney tissues. To determine the growth performance and disease resistant of Oreochromis sp. supplemented with herbal-mixed of the selected herbal extracts, the fish were fed with diet containing mixtures of AVE&VTE, VTE&SCE, SCE&AVE. Herbal mixed of AVE&VTE showed the most significant increased as compared with others. For SGR, only AVE&VTE showed promising result with significant higher (P< 0.05) than control. Fish survival after the disease challenge showed significant difference (P< 0.05) compared to control. In haematological assays, the post-challenged results showed the significant increased (P<0.05) of RBC, Hb and PCV values. The WBC value in pre- and post-challenged showed no significant different (P>0.05) of all treatments compared to control. As for MCHC value reading with the mixed-herbals, AVE&SCE was the only treatment which revealed no significant difference (P>0.05) in pre-challenged and showed decreased significant difference (P<0.05) in post-challenged in all treatments. On the other hand, MCV and plasma protein values did not show any significant difference (P>0.05) as compared to control. The biochemical parameters of ALT value and AST value were significantly affected by mixed-herbal supplementation. However in the post-challenged, the ALP value showed no significant difference compared to control. Histopathological changes, which included necrosis and haemorrhage in the kidney, liver and hepatopancreas tissues could be due to the cytotoxin produced by the bacteria. Also, a study was carried out to evaluate the effects of dietary supplementation of methanol extracts of V. trifolia, S. crispus and A. vera Oreochromis sp. as disease treatment. Results showed that RBC levels were significantly increased (P<0.05) in VTE-2, SCE-2, SCE-5, SCE-9, AVE-5, AVE-7 and control (OTC) as compared to control (infected). While, Hb value showed significant increased in VTE-2, SCE-5, SCE-9, in contrast to significant decreased in AVE-7 and AVE- 9 as compared to control. For PCV value showed significant (P<0.05) increased in all treatments included control (OTC) as compared to control (infected). On the other hand, in MCHC value no significant different for SCE-5. Plasma protein value showed significant increased (P<0.05) after supplementation of VTE-2, VTE-5, SCE-2, SCE-5, SCE-9, AVE-2, AVE-5, AVE-9. For ALT and AST values, they showed significant decrease in all treatments including control (uninfected) and control (OTC) (P<0.05). Also in ALP value, it showed significant decreased in all treatments including the control (OTC). The survivability of fish showed increase after fed with the herbal supplementation (P< 0.05) in VTE-5, VTE-7, AVE-2, AVE-5 and AVE-9 as compared to control (infected). All the haematological measurements in Oreochromis sp. that were infected with S. agalactiae with supplemented with VTE, SCE and AVE showed similar values compared with the control and the treatment with antibiotic. Its indicated the fish that were infected with S. agalactiae able to restore their haematological indices to near normal values. The results were agreeable with literatures which reported the numerous efficacies of the use of herbal in aquaculture to control various bacterial pathogens. Also from current research findings, suggested that mixed herbal of methanolic-extract given to S. agalactiae infected Oreochromis sp. had a synergistic restorative effect on the hematological variables. In conclusion, current study suggested that V. trifolia, S. crispus and A. vera extracts and mixed herbal were effective as growth promoters and bacterial disease treatment in Oreochromis sp. It also proved the potential of the selected herbal plant as aquaculture therapeutant as they were environmental friendly and it showed negligible side effect in the intended fish.